DEKADENSI PEMILIHAN HAKIM AGUNG OLEH DPR RI - Pikahulan, Rustam Magun (Fakultas Syariah Institut Agama Islam Negeri Palu, 2020)
Abstract: The Plato's conception of the rule of law states that good governance is based on good law. The organization also spreads to the world of Supreme Court justices, the election caused a decadence to the institutional status of the House of Representatives as a people's representative in the government whose implementation was not in line with the decision of the Constitutional Court. Based on the decision of the Constitutional Court No.27/PUU-XI/2013 explains that the House of Representatives no longer has the authority to conduct due diligence and suitability (elect) to prospective Supreme Judges proposed by the Judicial Commission. The House of Representatives can only approve or disapprove candidates for Supreme Court Justices that have been submitted by the Judicial Commission. In addition, the proportion of proposed Supreme Court Justices from the judicial commission to the House of Representatives (DPR) has changed, whereas previously the Judicial Commission had to propose 3 (three) of each vacancy for the Justices, now it is only one of each vacant for Supreme Court Judges. by the Supreme Court. The House of Representatives no longer has the authority to conduct due diligence and suitability (elect) to prospective Supreme Judges proposed by the Judicial Commission. The House of Representatives can only